Optical Materials for High-efficiency Solar Cells: A Comparative Study - Ahmet Demir; Baran Akbulut; Hale Yilmaz (Yayasan Adra Karima Hubbi, 2024)
The demand for renewable energy sources has accelerated research into high-efficiency solar cells. Optical materials play a critical role in enhancing light absorption and overall energy conversion efficiency. Understanding the properties and performance of various optical materials is essential for optimizing solar cell technology. This study aims to compare different optical materials used in solar cells to evaluate their effectiveness in maximizing solar energy conversion. The focus is on identifying materials that offer superior optical characteristics and compatibility with existing solar cell technologies. A comparative analysis was conducted on several optical materials, including silicon dioxide (SiO2), titanium dioxide (TiO2), and organic polymers. The study involved synthesizing these materials and assessing their optical properties using UV-Vis spectroscopy and photoluminescence measurements. Efficiency tests were performed on solar cell prototypes incorporating these materials. The findings reveal that titanium dioxide exhibited the highest light absorption and photonic efficiency compared to silicon dioxide and organic polymers. Solar cells utilizing TiO2 demonstrated a significant increase in overall efficiency, achieving conversion rates of up to 22%. In contrast, organic polymers showed lower performance but offered advantages in flexibility and lightweight applications. This research highlights the importance of selecting appropriate optical materials to enhance solar cell efficiency. Titanium dioxide emerges as a leading candidate for high-performance solar cells, while organic polymers may provide alternative solutions for specific applications. Continued exploration of optical materials will be crucial for advancing solar technology and meeting global energy demands.